Fatigue crack propagation behavior in AISI 304 steel welded joints for cold‐stretched liquefied natural gas (LNG) storage tank at cryogenic temperatures. Issue 5 (9th May 2019) - Kim, J.H.; Yoon, D.H.; Kim, J.H.; Kim, H.C.; Kim, K.D.
Abstract: AISI304 steel welded joints are used in cold‐stretched liquefied natural gas (LNG) storage tanks used for storing and transporting of liquefied gases. Compared with a conventional liquefied natural gas storage tank, a cold‐stretched liquefied natural gas storage tank has many advantages such as reduced thickness, light weight, low cost and low energy consumption. However, liquefied natural gas storage tanks can be subjected to alternative loads at cryogenic temperatures; thus, it is important to investigate the fatigue crack propagation behavior in AISI 304 steel welded joints at cryogenic temperatures. Specimens were machined from a cold‐stretched liquefied natural gas storage tank with a welding structure. The crack length was determined using compliance method and confirmed by examination with traveling microscope. Fatigue crack propagation rates were evaluated at various stress ratios and temperatures. The fatigue crack growth rate of all specimens a little appears the effect of stress ratio, but it has a great influence at a cryogenic temperature. The fatigue crack growth rate of longitudinal welded joint is the fastest at room and cryogenic temperature. Fracture mechanism in the specimen is examined using a scanning electron microscope.